2019
DOI: 10.3390/pharmaceutics11110610
|View full text |Cite
|
Sign up to set email alerts
|

Development of Injectable PEGylated Liposome Encapsulating Disulfiram for Colorectal Cancer Treatment

Abstract: Disulfiram (DS), an anti-alcoholism medicine, shows strong anti-cancer activity in the laboratory, but the application in clinics for anti-cancer therapy has been limited by its prompt metabolism. Conventional liposomes have shown limited ability to protect DS. Therefore, the aim of this study is to develop PEGylated liposomes of DS for enhanced bio-stability and prolonged circulation. PEGylated liposomes were prepared using ethanol-based proliposome methods. Various ratios of phospholipids, namely: hydrogenat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
55
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(63 citation statements)
references
References 45 publications
8
55
0
Order By: Relevance
“…Diethyldithiocarbamate copper (II) (DDC-Cu) consists of two molecules of diethyldithiocarbamic acid (DDC), a disulfiram (DS) metabolite, with one ion of copper II [ 1 , 2 ]. DS, clinically used as an anti-alcoholism drug, has been recently shown to possess potent anticancer activities against a wide range of cancers including colon, breast, lung, prostate, ovarian, cervical and brain cancers [ 1 , 3 , 4 ]. Additionally, the anticancer activity of DS includes effective termination of drug-resistant cancer stem cells (CSCs) and reverses chemoresistance [ 3 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Diethyldithiocarbamate copper (II) (DDC-Cu) consists of two molecules of diethyldithiocarbamic acid (DDC), a disulfiram (DS) metabolite, with one ion of copper II [ 1 , 2 ]. DS, clinically used as an anti-alcoholism drug, has been recently shown to possess potent anticancer activities against a wide range of cancers including colon, breast, lung, prostate, ovarian, cervical and brain cancers [ 1 , 3 , 4 ]. Additionally, the anticancer activity of DS includes effective termination of drug-resistant cancer stem cells (CSCs) and reverses chemoresistance [ 3 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…DS, clinically used as an anti-alcoholism drug, has been recently shown to possess potent anticancer activities against a wide range of cancers including colon, breast, lung, prostate, ovarian, cervical and brain cancers [ 1 , 3 , 4 ]. Additionally, the anticancer activity of DS includes effective termination of drug-resistant cancer stem cells (CSCs) and reverses chemoresistance [ 3 , 5 ]. However, the biological instability of DS in bloodstream has severely limited its clinical use in anti-cancer therapy [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…The volume of tumor size was calculated as follows: V = L × W 2 /2, of which W corresponds to the width and L to the length. Seven days later, the average volume of tumor reached~100 mm 3 , mice were then randomly assigned into two groups and treated with or without disulfiram (50 mg/kg) daily for another 21…”
Section: Tumor Xenograft Mouse Modelmentioning
confidence: 99%
“…Recently, studies emphasized the anti-tumor activity of disulfiram in breast cancer, pancreatic ductal adenocarcinoma, colorectal cancer, prostate cancer, etc. [ 19 , 20 , 21 , 22 ]. It was shown that disulfiram inhibited the proliferation and migration of tumor cells, promoted apoptosis, and reduced the resistance of tumor cells against chemotherapy and radiotherapy by interfering with different intracellular signals (PI3K/Akt, NF-kB, MAPK, p97/NPL4, ALDH, and proteosome) [ 23 , 24 , 25 ], which highlighted the role of disulfiram in inhibiting the growth and metastasis of tumors [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, encapsulation systems such as b-CDs or liposomes provide a molecular shield for photolabile drugs, thereby delaying their photodegradation. 35,36 Therefore, our study compared and analyzed the photostability of Rubropunctatin on its own and with R-Liposome.…”
Section: Photostabilitymentioning
confidence: 99%